2018
DOI: 10.1017/s1474747218000057
|View full text |Cite
|
Sign up to set email alerts
|

Can't wait to get my pension: the effect of raising the female early retirement age on income, poverty and deprivation

Abstract: We estimate the impact of increasing the female early retirement age (ERA) on household living standards. Examining the increase in the female ERA from 60 to 63 in the UK, we find increased earnings only partially offset lost public pension income, leaving affected women's household incomes £32 per week lower on average. The proportional effect was substantially larger for women in lower income households. This increased the income poverty rate among affected women by 6.4 percentage points. We find no evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
(29 reference statements)
2
26
1
1
Order By: Relevance
“…These are similar effects on labour supply to those found byCribb and Emmerson (2019) and a little larger than those found byCribb et al (2016).…”
supporting
confidence: 86%
See 1 more Smart Citation
“…These are similar effects on labour supply to those found byCribb and Emmerson (2019) and a little larger than those found byCribb et al (2016).…”
supporting
confidence: 86%
“…The first is that the higher State Pension Age involves a reduction in state pension income paid to women who are no longer eligible for the state pension at age 60 and it is this income loss that is the cause of the effects observed Cribb and Emmerson (2019). estimate that state benefit income (including the state pension) falls by an average of £82 ($107) per week for 60-62 year old women for the period before they reached their higher State Pension Age as a result of the…”
mentioning
confidence: 99%
“…The final strand consists of a set of a current empirical studies that examine the short-run impacts of recent increases in the EEA that varied by birth cohort on labor force participation, poverty, and program participation of older individuals in other countries. This includes Atalay and Barrett (2015), who studied women in Australia, Staubli and Zweimüller (2013) and Manoli and Weber (2016), who studied men and women in Austria, and Cribb and Emmerson (2017), who studied women in the United Kingdom. Taken together, these studies show that for individuals close to the EEA (i.e., in their late 50s and early 60s) raising the EEA generates significant increases in participation in the labor force and other gateway social insurance programs (e.g., disability and unemployment insurance, with results differing somewhat across countries).…”
Section: Previous Literaturementioning
confidence: 99%
“…Taken together, these studies show that for individuals close to the EEA (i.e., in their late 50s and early 60s) raising the EEA generates significant increases in participation in the labor force and other gateway social insurance programs (e.g., disability and unemployment insurance, with results differing somewhat across countries). Cribb and Emmerson (2017) showed that raising the EEA actually raised the poverty rate in the short-run, because the increases in earnings and other program income were not enough to offset the loss of old-age pension benefits.…”
Section: Previous Literaturementioning
confidence: 99%
“…J. Cribb and C. Emmerson (2018) attempted to assess the impact of raising the retirement age on household living standards in the UK. In their study, they concluded that raising the retirement age from age 60 to 63 reduces the net income of women aged 60-62 years an average of £32 ($42) per week, and for women in low-income households, the poverty rate is higher by 6.4 percentage points.…”
Section: Review Of Literaturementioning
confidence: 99%